Postpartum abstinence and risk of HIV among young mothers in the kassena-nankana district of northern Ghana - Achana, F.S.; Debpuur, C.; Akweongo, P.; Cleland, J. (My University, 2010)
This study explored the role and shaping of postpartum abstinence on young mothers' sexual conduct and vulnerability to HIV infection in a rural setting of Northern Ghana. Young mothers in their mid-twenties to early-thirties and men married to young mothers were purposively selected for repeated semi-structured interviews. The interviews were tape-recorded, transcribed and Nvivo software was used to organize and manage the data for analysis. In this setting, postpartum abstinence was perceived as a risk period for STIs due to increased male infidelity during this period. Yet, women's urge to take action to mitigate the risk of STIs is compromised by childbearing obligations. More assertive women, however, employ crafty and nifty protective strategies including the masturbation of their male partner when they perceive themselves at risk. We conclude that the advent of HIV and AIDS, coupled with improved access to sexual and reproductive health information and modern contraception, has eroded the logic of observance of postpartum abstinence in the Kassena-Nankana District of Northern Ghana. Efforts should be made to facilitate easy access to modern contraceptives and HIV protection by rural women.